Nonviolent Peace Activism - Naar-Obed, Michele (Social justice, 2003)
Part of a special issue on war, dissent, and justice from the perspective of scholars, activists, and former U.S. political prisoners. The members of the Atlantic Life Community (ALC), a society of peace activists and Catholic Worker communities located on America's East Coast, view nonviolence as a way of life. The men and women of the ALC use their faith as an agitator and a catalyst for direct action, and many of its number are committed to challenging the nation's government about the crimes that it commits at home and around the world. Everyone in the country could take part in a national strike against the military economy through actions such as civil disobedience and nonviolent direct action.